Correlation Between Students’ Passive Vocabulary Mastery and Reading Comprehension at Public School in Kudus - Febriani, Calvina Izumi; Madjdi, Achmad Hilal; Surachmi, Sri (Universitas Muria Kudus, 2025)
Mastering vocabulary naturally aids students in the use of and examining the four language skills including listening, speaking, reading, and writing. As a result, there is a precise hyperlink between vocabulary knowledge and language capability performance. Therefore, this study aimed to know the relationship between students' passive vocabulary mastery and reading comprehension at Public School in Kudus. The quantitative method design was used in this research. The subject of this research was 30 students who were randomly selected. The instruments used were multiple-choice tests to measure passive vocabulary acquisition and reading comprehension. The data were analyzed using Pearson Product-Moment Correlation with the help of SPSS 25. The results showed a positive and significant correlation between passive vocabulary mastery and reading comprehension, with a correlation coefficient (r) of 0.533. This indicates that students' reading comprehension of English literature improves with their level of passive vocabulary acquisition. It means that the development of students’ vocabulary mastery is important to their reading comprehension. Therefore, teachers could implement more strategies that ultimately supporting students in becoming stronger and more confident readers. In addition, future researcher provides more nuanced insights into the relationship between passive vocabulary and reading comprehension on their research.